Kompetensi dan Interaksi Kompetensi Lulusan D-III Bahasa Inggris Minat Profesi Administrasi Bisnis dan Hubungan Masyarakat - Wahyu Kartika Wienanda; Nur Endah Nugraheni; Erlin Estiana Yuanti (JLA (Jurnal Lingua Applicata), 2018)
Concrete and practical competencies matching the workforce needs have an essential role in constructing the employability of the graduates, especially during MEA era where the graduates are expected to compete internationally. To accommodate this purpose, D-III English SV-UGM provides a number of professional concentrations for the students, including Business Administration (BA) and Public Relation (PR) to give them practical skills that are applicable in the workforce. In light of this circumstance, the present research aims at remapping the graduate competencies to be mastered by the students of D-III English concentrating on BA and PR and revealing the intersections of the competencies. Library study, questionnaire administration, and interview were conducted to obtain the data from the stakeholders. The results show that the graduates concentrating in BA are highly expected to give excellent service to the clients and customers, to maintain documents and letters, and have a good archival knowledge. Meanwhile, the graduates with PR concentration should be able to have good communication skills and understanding about the computer and media use. Furthermore, the graduates from both concentrations are expected to perform Occupational Health and Safety Environment, and have a good interpersonal skill to enable them to work effectively with their colleagues.